2017
DOI: 10.1097/ta.0000000000001322
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spine MRI in patients with negative CT

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Comparative multicenter prospective studies were able to show in a selected patient population that MRI examination identified additional pathological findings in 23.6 % of cases with inconspicuous CT examination of the cervical spine. However, they did not evaluate the clinical significance of the injuries 28 . However, at present, continuous availability of MRI examination is not specified as a requirement for trauma centers in the current White Book on Medical Care of the Severely Injured 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative multicenter prospective studies were able to show in a selected patient population that MRI examination identified additional pathological findings in 23.6 % of cases with inconspicuous CT examination of the cervical spine. However, they did not evaluate the clinical significance of the injuries 28 . However, at present, continuous availability of MRI examination is not specified as a requirement for trauma centers in the current White Book on Medical Care of the Severely Injured 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Prinzipiell wird eine MRT-Untersuchung bei fraglichen CT-Befunden, wie etwa der traumatischen Dissektion von Vertebralarterien oder Pathologien der Wirbelsäule im Sinne einer Rückenmarksschädigung angefordert. Vergleichende multizentrische prospektive Studien konnten in einer selektionierten Patientenpopulation nachweisen, dass durch eine MRT in 23,6 % der Fälle bei unauffälligem CT der Halswirbelsäule zusätzliche pathologische Befunde entdeckt wurden, ohne die klinische Signifikanz der Verletzungen zu evaluieren 28 . Gegenwärtig ist das Vorhalten von MRT-Untersuchungen zu jeder Tageszeit jedoch keine Bedingung, die im aktuellen Weißbuch der Schwerverletztenversorgung als Anforderung für TraumaZentren vorgeschrieben ist 9 .…”
Section: Diskussionunclassified
“…However, in the obtunded or unreliable patient, further MRI imaging may be warranted because of a limited clinical examination. 29…”
Section: Computed Tomography (Ct)/magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…The ReCONECT trial by Maung and colleagues showed that in awake, oriented patients with a negative CT, MRI imaging failed to alter treatment course from nonoperative to operative management. However, in the obtunded or unreliable patient, further MRI imaging may be warranted because of a limited clinical examination 29…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…However, trauma patients may often fail to meet one or more requirements needed to remove the cervical collar (c-collar) as, for example, both guidelines require a normal level of alertness. In these NEXUS-positive patients, further examination will involve computed tomography (CT), and it is generally accepted that a c-collar can be removed following a negative CT of the cervical spine (CTCS) if no neurological deficits are apparent [3][4][5]. The evidence supporting this practice, however, is purely observational [6].…”
Section: Introductionmentioning
confidence: 99%